High-alkali-resistant nanofiber bipolar membrane and preparation method thereof
Patent Information
- Application Number
- CN202611470689.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
1、阳离子层依靠三氯化铁浸泡引入Fe3+催化剂,仅依靠羧基弱配位结合;长期通电运行条件下铁离子容易发生迁移流失,水解离催化能力逐步衰减,跨膜电压持续升高,膜使用寿命受限
1、铁离子多重螯合锚定:氨基改性氧化石墨烯与单宁酸配位,显著抑制运行过程Fe3+溶出流失;长时间循环老化后跨膜电压上升幅度显著降低,延长双极膜使用寿命。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrodialysis ion exchange membrane technology, specifically relating to a high alkali-resistant nanofiber bipolar membrane and its preparation method, which can be applied to electrodialysis processes such as acid and alkali production from salt solution dissociation, organic acid purification, and salt lake resource recovery. Background Technology
[0002] Bipolar films can hydrolyze interfacial water into H+ under an applied DC electric field. + With OH - It is widely used in electrodialysis for acid and alkali production and wastewater resource utilization.
[0003] CN121422740B discloses an electrospun nanofiber-reinforced bipolar membrane, which uses three electrospinning processes to prepare an intermediate layer, a cationic nanofiber layer, and a chitosan-PVA anionic nanofiber layer, respectively. Branched anionic polyacrylamide is used to improve spinning performance, modified graphene oxide is used to optimize fiber morphology, and ferric chloride is crosslinked to introduce Fe. 3+ Glutaraldehyde is used as a water dissociation catalyst to crosslink the anion layer via vapor. This method can yield bipolar membranes with lower transmembrane voltages, but several key technical shortcomings remain: 1. The cation layer is introduced by immersion in ferric chloride to introduce Fe. 3+ The catalyst relies solely on weak coordination of carboxyl groups; under long-term energized operation, iron ions are prone to migration and loss, the catalytic ability of water dissociation gradually declines, the transmembrane voltage continues to rise, and the membrane lifespan is limited.
[0004] 2. The anion exchange layer adopts a chitosan-polyvinyl alcohol system. Chitosan amino groups are easily degraded in high-concentration strong alkaline environments, and their alkali resistance is insufficient, making it difficult to adapt to industrial conditions with high alkali output.
[0005] 3. The three layers of nanofibers are electrospun and stacked in sequence. The layers rely solely on physical stacking. Under repeated swelling and shrinkage cycles, the layers are prone to delamination, resulting in insufficient mechanical stability of the membrane.
[0006] 4. The entire structure is composed of highly porous nanofiber networks. Under high current density, salt counterions are prone to transmembrane leakage, which reduces the purity of acid and alkali production.
[0007] 5. The process uses a nickel mesh receiving substrate, which makes membrane peeling difficult; glutaraldehyde vapor crosslinking is highly toxic, the efficiency of three-stage electrospinning is low, batch repeatability is poor, and it is difficult to achieve industrial scale-up.
[0008] 6. Existing technologies lack post-processing methods for pore densification, and excessively large pores in nanofiber membranes can lead to counterion leakage problems.
[0009] Therefore, it is necessary to develop a nanofiber-reinforced bipolar membrane with a highly alkali-resistant anion layer, interlayer bonding to prevent delamination, reduced counterion leakage, and ease of fabrication. Summary of the Invention
[0010] To address the shortcomings of existing technologies, a highly alkali-resistant nanofiber bipolar membrane and its preparation method are proposed, which improves the alkali degradation resistance of the anion layer and enables it to adapt to electrodialysis conditions with high concentrations of alkali.
[0011] The objective of this invention can be achieved through the following technical solutions: A method for preparing a highly alkali-resistant nanofiber bipolar membrane, characterized by comprising the following steps: S0, Raw material pre-preparation: I. Preparation of branched anionic polyacrylamide, wherein the branched anionic polyacrylamide comprises the following raw materials, by mass parts: 8-12 parts acrylamide, 0.05-0.07 parts chain transfer agent, 1.1-1.2 parts N,N'-methylenebisacrylamide, 0.02-0.03 parts ammonium persulfate, and 6-8 parts anionic monomer; the preparation method includes the following steps: under a nitrogen atmosphere, acrylamide and chain transfer agent are added to an acetate buffer solution with a pH of 5±0.1, mixed evenly, and deoxygenated to obtain a reaction monomer solution; N,N'-methylenebisacrylamide is prepared into a crosslinking agent solution using deionized water; the reaction monomer solution is heated to 55-65℃, ammonium persulfate is added, and the crosslinking agent solution is added dropwise, controlling the dropwise addition time to be 2-2.5h; after completion, the anionic monomer is added, and the reaction is stirred at 55-65℃ for 2-3h; the mixture is washed, purified, and dried to obtain branched anionic polyacrylamide; II. Preparation of amino-functionalized graphene oxide: A large number of amino sites are grafted onto the surface of the amino-functionalized graphene oxide for anchoring Fe. 3+ ion; III. Preparation of quaternized modified chitosan: Quaternization grafting modification of chitosan to improve the alkali resistance of the anion layer; S1. Preparation of intermediate layer spinning solution: by mass, 1-3 parts of branched anionic polyacrylamide, 3-5 parts of linear anionic polyacrylamide, 0.3-0.5 parts of amino-functionalized modified graphene oxide, and the remainder is 50-60 wt% aqueous acetic acid solution. Electrospinning is used to spin an intermediate nanofiber substrate film on the surface of the aluminum foil receiving substrate; the nanofiber film is easy to peel off from the aluminum foil substrate in the future. S2. Preparation of cationic layer spinning solution: 2-4 parts linear anionic polyacrylamide, the remainder 50-60 wt% aqueous acetic acid solution; electrospinning deposition of cationic precursor nanofiber layer on the first side of intermediate nanofiber substrate membrane; subsequently immersing in ferric chloride ethanol solution containing chelating agent, tannic acid is selected as the chelating agent; Fe 3+On the one hand, crosslinked polyacrylamide is formed, and on the other hand, it forms multiple chelate coordination with amino-modified graphene oxide and tannic acid to achieve firm anchoring of iron ions and inhibit the dissolution and loss of iron ions during operation; after washing and drying, a cationic nanofiber layer is obtained; the intermediate layer and the cationic layer undergo molecular chain interdiffusion during the spinning-crosslinking process to form interlayer interlocking. S3. Prepare the anion exchange spinning solution: 7-8 parts polyvinyl alcohol, 1-1.5 parts quaternized modified chitosan, and the remainder is 50-60 wt% aqueous acetic acid solution; electrospin-deposit the anion precursor nanofiber layer on the second side of the intermediate nanofiber substrate membrane; use liquid-phase glutaraldehyde immersion crosslinking to avoid glutaraldehyde vapor process; during crosslinking, glutaraldehyde reacts with the polymer chains of the intermediate layer and the anion and cation layers simultaneously, forming covalent chemical bonds between the three layers and inhibiting interlayer delamination; wash and dry to obtain the anion nanofiber layer; S4. Post-treatment for controllable densification of pores: The three-layer composite nanofiber membrane is obtained by immersion in glycerol-water solution and low-temperature hot pressing to achieve controllable densification of the nanofiber network pores, retaining the internal three-dimensional interface while reducing the large pore size and reducing counterion transmembrane leakage; the hot pressing temperature is 45-60℃ and the pressure is 0.2-0.5MPa. S5. Peeling: Completely peel the composite film from the aluminum foil receiving substrate; soak and activate to obtain a highly alkali-resistant nanofiber bipolar film.
[0012] Furthermore, in step S1, during the electrospinning process, the voltage is 20-25kV, the flow rate is 0.3-0.5mL / h, the receiving distance is 15-20mm, and the humidity is 50-60%.
[0013] Furthermore, in steps S2 and S3, during the electrospinning process, the voltage is 15-20kV, the flow rate is 0.5-1mL / h, the receiving distance is 10-15mm, and the humidity is 50-60%.
[0014] Furthermore, in step S0, the branched anionic polyacrylamide raw material ratio is: anionic monomers in a mass ratio of 8:2-3 acrylic acid and allyl malonic acid.
[0015] Furthermore, in step S0, during the preparation of the amino-functionalized modified graphene oxide, the graphene oxide is first alkenylated, then grafted with amino-containing monomers, resulting in a surface rich in amino chelation sites and multiple chelation fixation of Fe. 3+ .
[0016] Furthermore, in step S0, the quaternized chitosan is modified with 2,3-epoxypropyltrimethylammonium chloride grafted onto chitosan to improve its alkali resistance and anion exchange sites.
[0017] Furthermore, in step S2, the mass fraction of FeCl3 in the ferric chloride ethanol solution is 8-10 wt%, and the amount of tannic acid added is 15-25 wt% of the mass of FeCl3; the crosslinking time is 10-12 min.
[0018] Furthermore, in step S3, during the glutaraldehyde liquid phase immersion crosslinking process, 45-50 wt% of glutaraldehyde aqueous solution is used for immersion for 8-10 min.
[0019] This invention also discloses a highly alkali-resistant nanofiber bipolar membrane product: A highly alkali-resistant nanofiber bipolar membrane is prepared by the above method; the membrane comprises: an intermediate nanofiber layer, a cationic nanofiber layer, and an anionic nanofiber layer; covalently bonded interfaces exist between the three layers; amino-functionalized modified graphene oxide is dispersed inside the intermediate layer, and Fe... 3+ The membrane is anchored on modified graphene oxide through multiple chelation sites; the anionic layer is a quaternized modified chitosan-polyvinyl alcohol crosslinked network; the membrane undergoes low-temperature hot pressing densification treatment; the membrane porosity is 35-50%.
[0020] The highly alkali-resistant nanofiber bipolar membrane and its preparation method have the following beneficial effects: 1. Multiple chelation anchoring of iron ions: The coordination of amino-modified graphene oxide with tannic acid significantly inhibits the Fe ion concentration during operation. 3+ Leaching loss; after long-term cyclic aging, the rise in transmembrane voltage is significantly reduced, extending the service life of the bipolar membrane.
[0021] 2. The quaternized modified chitosan anionic layer is resistant to strong alkali degradation and can be used in high-concentration sodium hydroxide production conditions, expanding industrial application scenarios.
[0022] 3. Glutaraldehyde liquid-phase crosslinking forms covalent chemical bonds between the three membrane layers. Under repeated swelling and contraction conditions in the electrolyte, the layers are not easily delaminated, thus improving the mechanical stability of the membrane.
[0023] 4. The aluminum foil receiving substrate makes the finished film easy to peel off completely without tearing the nanofiber membrane; liquid phase glutaraldehyde immersion replaces the toxic vapor process, and the process conditions are easier to scale up industrially.
[0024] 5. Low-temperature and low-pressure hot-pressing densification treatment reduces the size of large-sized through-pores while preserving the three-dimensional fiber hydrolysis interface, thereby reducing salt counterion transmembrane leakage and improving the purity of acid and alkali products. Detailed Implementation
[0025] Example 1 The preparation method of this highly alkali-resistant nanofiber bipolar membrane includes the following steps: S0, Raw material pre-preparation: I. Preparation of branched anionic polyacrylamide, wherein the branched anionic polyacrylamide comprises the following raw materials, by mass parts: 8-12 parts acrylamide, 0.05-0.07 parts chain transfer agent, 1.1-1.2 parts N,N'-methylenebisacrylamide, 0.02-0.03 parts ammonium persulfate, and 6-8 parts anionic monomer; the preparation method includes the following steps: under a nitrogen atmosphere, acrylamide and chain transfer agent are added to an acetate buffer solution with a pH of 5±0.1, mixed evenly, and deoxygenated to obtain a reaction monomer solution; N,N'-methylenebisacrylamide is prepared into a crosslinking agent solution using deionized water; the reaction monomer solution is heated to 55-65℃, ammonium persulfate is added, and the crosslinking agent solution is added dropwise, controlling the dropwise addition time to be 2-2.5h; after completion, the anionic monomer is added, and the reaction is stirred at 55-65℃ for 2-3h; the mixture is washed, purified, and dried to obtain branched anionic polyacrylamide; II. Preparation of amino-functionalized graphene oxide: A large number of amino sites are grafted onto the surface of the amino-functionalized graphene oxide for anchoring Fe. 3+ ion; III. Preparation of quaternized modified chitosan: Quaternization grafting modification of chitosan to improve the alkali resistance of the anion layer; S1. Preparation of intermediate layer spinning solution: by mass, 1-3 parts of branched anionic polyacrylamide, 3-5 parts of linear anionic polyacrylamide, 0.3-0.5 parts of amino-functionalized modified graphene oxide, and the remainder is 50-60 wt% aqueous acetic acid solution. Electrospinning is used to spin an intermediate nanofiber substrate film on the surface of the aluminum foil receiving substrate; the nanofiber film is easy to peel off from the aluminum foil substrate in the future. S2. Preparation of cationic layer spinning solution: 2-4 parts linear anionic polyacrylamide, the remainder 50-60 wt% aqueous acetic acid solution; electrospinning deposition of cationic precursor nanofiber layer on the first side of intermediate nanofiber substrate membrane; subsequently immersing in ferric chloride ethanol solution containing chelating agent, tannic acid is selected as the chelating agent; Fe 3+ On the one hand, crosslinked polyacrylamide is formed, and on the other hand, it forms multiple chelate coordination with amino-modified graphene oxide and tannic acid to achieve firm anchoring of iron ions and inhibit the dissolution and loss of iron ions during operation; after washing and drying, a cationic nanofiber layer is obtained; the intermediate layer and the cationic layer undergo molecular chain interdiffusion during the spinning-crosslinking process to form interlayer interlocking. S3. Prepare the anion exchange spinning solution: 7-8 parts polyvinyl alcohol, 1-1.5 parts quaternized modified chitosan, and the remainder is 50-60 wt% aqueous acetic acid solution; electrospin-deposit the anion precursor nanofiber layer on the second side of the intermediate nanofiber substrate membrane; use liquid-phase glutaraldehyde immersion crosslinking to avoid glutaraldehyde vapor process; during crosslinking, glutaraldehyde reacts with the polymer chains of the intermediate layer and the anion and cation layers simultaneously, forming covalent chemical bonds between the three layers and inhibiting interlayer delamination; wash and dry to obtain the anion nanofiber layer; S4. Post-treatment for controllable densification of pores: The three-layer composite nanofiber membrane is obtained by immersion in glycerol-water solution and low-temperature hot pressing to achieve controllable densification of the nanofiber network pores, retaining the internal three-dimensional interface while reducing the large pore size and reducing counterion transmembrane leakage; hot pressing temperature 45℃, pressure 0.25MPa; S5. Peeling: Completely peel the composite film from the aluminum foil receiving substrate; soak and activate to obtain a highly alkali-resistant nanofiber bipolar film.
[0026] In step S1, during the electrospinning process, the voltage is 20-25kV, the flow rate is 0.3-0.5mL / h, the receiving distance is 15-20mm, and the humidity is 50-60%.
[0027] In steps S2 and S3, during the electrospinning process, the voltage is 15-20kV, the flow rate is 0.5-1mL / h, the receiving distance is 10-15mm, and the humidity is 50-60%.
[0028] In step S0, the branched anionic polyacrylamide raw material ratio is: anionic monomers in a mass ratio of 8:2-3 acrylic acid and allyl malonic acid.
[0029] In step S0, during the preparation of the amino-functionalized modified graphene oxide, the graphene oxide is first alkenylated, then grafted with amino-containing monomers, resulting in a surface rich in amino chelation sites and multiple chelation fixation of Fe. 3+ .
[0030] In step S0, the quaternized chitosan is modified with 2,3-epoxypropyltrimethylammonium chloride grafted onto chitosan to improve its alkali resistance and anion exchange sites.
[0031] In step S2, the FeCl3 mass fraction in the ferric chloride ethanol solution is 8 wt%, and the tannic acid added is 15 wt% of the FeCl3 mass; the crosslinking time is 10 min.
[0032] In step S3, during the glutaraldehyde liquid phase immersion crosslinking process, 45wt% glutaraldehyde aqueous solution is used for immersion for 8 minutes.
[0033] The high alkali-resistant nanofiber bipolar membrane product prepared by the above method includes an intermediate nanofiber layer, a cationic nanofiber layer, and an anionic nanofiber layer; there are covalently bonded interfaces between the three layers; amino-functionalized modified graphene oxide is dispersed inside the intermediate layer, Fe... 3+ The membrane is anchored on modified graphene oxide through multiple chelation sites; the anionic layer is a quaternized modified chitosan-polyvinyl alcohol crosslinked network; the membrane undergoes low-temperature hot pressing densification treatment; the membrane porosity is 35%. Example
[0034] The preparation method of this highly alkali-resistant nanofiber bipolar membrane includes the following steps: S0, Raw material pre-preparation: I. Preparation of branched anionic polyacrylamide, wherein the branched anionic polyacrylamide comprises the following raw materials, by mass parts: 8-12 parts acrylamide, 0.05-0.07 parts chain transfer agent, 1.1-1.2 parts N,N'-methylenebisacrylamide, 0.02-0.03 parts ammonium persulfate, and 6-8 parts anionic monomer; the preparation method includes the following steps: under a nitrogen atmosphere, acrylamide and chain transfer agent are added to an acetate buffer solution with a pH of 5±0.1, mixed evenly, and deoxygenated to obtain a reaction monomer solution; N,N'-methylenebisacrylamide is prepared into a crosslinking agent solution using deionized water; the reaction monomer solution is heated to 55-65℃, ammonium persulfate is added, and the crosslinking agent solution is added dropwise, controlling the dropwise addition time to be 2-2.5h; after completion, the anionic monomer is added, and the reaction is stirred at 55-65℃ for 2-3h; the mixture is washed, purified, and dried to obtain branched anionic polyacrylamide; II. Preparation of amino-functionalized graphene oxide: A large number of amino sites are grafted onto the surface of the amino-functionalized graphene oxide for anchoring Fe. 3+ ion; III. Preparation of quaternized modified chitosan: Quaternization grafting modification of chitosan to improve the alkali resistance of the anion layer; S1. Preparation of intermediate layer spinning solution: by mass, 1-3 parts of branched anionic polyacrylamide, 3-5 parts of linear anionic polyacrylamide, 0.3-0.5 parts of amino-functionalized modified graphene oxide, and the remainder is 50-60 wt% aqueous acetic acid solution. Electrospinning is used to spin an intermediate nanofiber substrate film on the surface of the aluminum foil receiving substrate; the nanofiber film is easy to peel off from the aluminum foil substrate in the future. S2. Preparation of cationic layer spinning solution: 2-4 parts linear anionic polyacrylamide, the remainder 50-60 wt% aqueous acetic acid solution; electrospinning deposition of cationic precursor nanofiber layer on the first side of intermediate nanofiber substrate membrane; subsequently immersing in ferric chloride ethanol solution containing chelating agent, tannic acid is selected as the chelating agent; Fe 3+On the one hand, crosslinked polyacrylamide is formed, and on the other hand, it forms multiple chelate coordination with amino-modified graphene oxide and tannic acid to achieve firm anchoring of iron ions and inhibit the dissolution and loss of iron ions during operation; after washing and drying, a cationic nanofiber layer is obtained; the intermediate layer and the cationic layer undergo molecular chain interdiffusion during the spinning-crosslinking process to form interlayer interlocking. S3. Prepare the anion exchange spinning solution: 7-8 parts polyvinyl alcohol, 1-1.5 parts quaternized modified chitosan, and the remainder is 50-60 wt% aqueous acetic acid solution; electrospin-deposit the anion precursor nanofiber layer on the second side of the intermediate nanofiber substrate membrane; use liquid-phase glutaraldehyde immersion crosslinking to avoid glutaraldehyde vapor process; during crosslinking, glutaraldehyde reacts with the polymer chains of the intermediate layer and the anion and cation layers simultaneously, forming covalent chemical bonds between the three layers and inhibiting interlayer delamination; wash and dry to obtain the anion nanofiber layer; S4. Post-treatment for controllable densification of pores: The three-layer composite nanofiber membrane is obtained by soaking in glycerol-water solution and hot pressing at low temperature to achieve controllable densification of the nanofiber network pores, retaining the internal three-dimensional interface while reducing the large pore size and reducing counterion transmembrane leakage; hot pressing temperature is 60℃ and pressure is 0.45MPa. S5. Peeling: Completely peel the composite film from the aluminum foil receiving substrate; soak and activate to obtain a highly alkali-resistant nanofiber bipolar film.
[0035] In step S1, during the electrospinning process, the voltage is 20-25kV, the flow rate is 0.3-0.5mL / h, the receiving distance is 15-20mm, and the humidity is 50-60%.
[0036] In steps S2 and S3, during the electrospinning process, the voltage is 15-20kV, the flow rate is 0.5-1mL / h, the receiving distance is 10-15mm, and the humidity is 50-60%.
[0037] In step S0, the branched anionic polyacrylamide raw material ratio is: anionic monomers in a mass ratio of 8:2-3 acrylic acid and allyl malonic acid.
[0038] In step S0, during the preparation of the amino-functionalized modified graphene oxide, the graphene oxide is first alkenylated, then grafted with amino-containing monomers, resulting in a surface rich in amino chelation sites and multiple chelation fixation of Fe. 3+ .
[0039] In step S0, the quaternized chitosan is modified with 2,3-epoxypropyltrimethylammonium chloride grafted onto chitosan to improve its alkali resistance and anion exchange sites.
[0040] In step S2, the FeCl3 mass fraction in the ferric chloride ethanol solution is 10 wt%, and the tannic acid added is 25 wt% of the FeCl3 mass; the crosslinking time is 12 min.
[0041] In step S3, during the glutaraldehyde liquid phase immersion crosslinking process, 50wt% glutaraldehyde aqueous solution is used for immersion for 10 minutes.
[0042] The high alkali-resistant nanofiber bipolar membrane product prepared by the above method includes an intermediate nanofiber layer, a cationic nanofiber layer, and an anionic nanofiber layer; there are covalently bonded interfaces between the three layers; amino-functionalized modified graphene oxide is dispersed inside the intermediate layer, Fe... 3+ The membrane is anchored on modified graphene oxide through multiple chelation sites; the anionic layer is a quaternized modified chitosan-polyvinyl alcohol crosslinked network; the membrane undergoes low-temperature hot pressing densification treatment; the membrane porosity is 45%.
[0043] Five performance tests comparison 1. IV curves and transmembrane voltages at different current densities.
[0044] Test conditions: Four-compartment electrodialysis apparatus; cathode / anode compartment: 0.5 mol / L Na2SO4; initial acid / base compartment: 0.5 mol / L NaCl; room temperature 25℃, peristaltic pump speed 60 r / min; gradually increase the current density, and record the corresponding transmembrane voltage after the voltage reading stabilizes.
[0045] Sample Description: Comparative example: Ordinary chitosan-PVA bipolar membrane (no chelation anchoring, no densification) Example 1: The basic formulation of the membrane of the present invention (amino-modified graphene oxide, tannic acid chelation, quaternized chitosan, densification post-treatment) Example 2: Optimized membrane of the present invention (chelation and densification processes further optimized) Table 1 10 1.21 1.18 1.16 30 1.56 1.31 1.29 50 1.74 1.52 1.41 80 2.13 1.62 1.51 The IV curve reflects the water dissociation characteristics of bipolar membranes; the inflection point corresponds to the water dissociation onset voltage; at the same current density, the lower the transmembrane voltage, the lower the membrane water dissociation energy consumption. A four-compartment electrodialysis test apparatus was used, with the cathode and anode compartments filled with 0.5 mol / L sodium sulfate solution, and the acid and alkali compartments filled with an initial concentration of 0.5 mol / L sodium chloride solution; the peristaltic pump circulation speed was set at 60 r / min, and the membrane IV characteristics were tested at room temperature (25℃). The current density was set from 10 mA / cm². 2 Gradually increase to 150mA / cm 2 After each current adjustment, once the system voltage reading stabilizes, the transmembrane voltage corresponding to each current density is recorded. The test results are shown in Table 1 above.
[0046] The comparative example is the original nanofiber bipolar membrane; Examples 1 and 2 are bipolar membranes prepared according to the present invention. As can be seen from the test data, the transmembrane voltage of the samples from the examples of the present invention is lower than that of the comparative example throughout the entire tested current density range. Although the present invention introduces a glycerol immersion-low-temperature, low-pressure hot-pressing densification treatment to regulate membrane porosity, it does not significantly increase the transmembrane voltage; thanks to the abundant three-dimensional water dissociation interfaces constructed by amino-functionalized modified graphene oxide, the membrane still maintains a low water dissociation voltage. At a high current density of 150 mA / cm², [the membrane exhibits this characteristic]. 2 Under the specified conditions, the transmembrane voltage in the comparative example reached 3.15V, in Example 1 it was 2.96V, and in Example 2 it was only 2.88V. This indicates that the present invention maintains excellent water dissociation performance while achieving pore densification and suppressing counterion leakage, making it suitable for industrial electrodialysis conditions with high current densities.
[0047] 2. Rates of acid and alkali production and product purity.
[0048] Test conditions: Four-compartment electrodialysis apparatus; constant current density 50 mA / cm² 2 Cathode and anode chambers: 0.5 mol / L Na₂SO₄; Acid and alkali chambers: initial solution 0.5 mol / L NaCl; room temperature 25℃, peristaltic pump speed 60 r / min; continuous operation for 60 min, sampling and testing of H₂ in the acid chamber. + Concentration, alkali chamber OH - Concentration, and simultaneous detection of Na in the acid chamber + Alkali chamber Cl - Counterion content is used to calculate acid production rate, alkali production rate, and product purity.
[0049] Sample Description: Comparative examples: ordinary chitosan-PVA bipolar membrane, without pore densification post-treatment, and high-porosity nanofiber original membrane; Example 1: The basic formulation of this invention, amino-modified graphene oxide, and tannic acid chelate anchoring Fe. 3+ Quaternized chitosan, glycerol soaking, and low-temperature, low-pressure hot pressing densification treatment; Example 2: The present invention optimizes the proportions and optimizes the hot pressing process parameters based on Example 1, further optimizing the porosity.
[0050] Table 2 Comparative Example 0.331 0.327 76.2 75.4 The fiber membrane has large pores, leading to significant leakage of salt counterions across the membrane; the purity of acid and alkali products is low; the acid and alkali production rates are acceptable, but the products are severely contaminated by salt ions. Example 1 (Basic formulation of the present invention, densification treatment) 0.324 0.32 91.5 90.8 While preserving the three-dimensional water dissociation interface resulted in a slight decrease in the rates of acid and alkali production, counterion leakage was significantly suppressed, and the purity of acid and alkali products was greatly improved. Example 2 (Optimized formulation and densification process of this invention) 0.32 0.317 93.3 92.6 With improved pore size control, counterion leakage is further reduced, resulting in the highest product purity; the water dissociation rate is only slightly sacrificed. A four-compartment electrodialysis apparatus was used. The cathode and anode chambers were filled with 0.5 mol / L sodium sulfate solution, while the acid and alkali chambers were initially filled with 0.5 mol / L sodium chloride solution. The peristaltic pump was set to circulate at 60 r / min, and the constant current density was 50 mA / cm². 2The experiment was run continuously for 60 minutes at room temperature. After the experiment, solutions from the acid and alkali chambers were taken and the concentrations of hydrogen ions and hydroxide ions were determined by titration. The contents of sodium ions in the acid chamber and chloride ions and counterions in the alkali chamber were detected by ion chromatography. The acid production rate, alkali production rate, acid product purity, and alkali product purity were calculated.
[0051] The test results are shown in Table 2 above. The comparative example is the original nanofiber bipolar membrane, which has not undergone pore densification treatment. The nanofiber network has a large number of interconnected macropores. Under the drive of the electric field, salt ions on the feed side can easily pass through the membrane pores and cause transmembrane leakage. Although it has considerable acid and alkali production rates, the acid chamber is mixed with a large number of sodium ions and the alkali chamber is mixed with a large number of chloride ions. The purity of the acid product is only 76.2% and the purity of the alkali product is only 75.4%. The products are contaminated by salt impurities, which is not conducive to subsequent industrial use.
[0052] This invention employs a controlled densification process involving glycerol soaking followed by low-temperature, low-pressure hot pressing. This effectively seals the large pores within the membrane and inhibits the transmembrane migration of salt counterions while preserving the three-dimensional water dissociation interface of the nanofibers and maintaining a high rate of acid and alkali production. In Example 1, the purity of the acid product reached 91.5%, and the purity of the alkali product reached 90.8%. In Example 2, after optimizing the densification process, the purity of the acid product reached 93.3%, and the purity of the alkali product reached 92.6%. This invention achieves a balance between water dissociation efficiency and high product purity, making it more suitable for industrial applications involving the preparation of high-purity acids and alkalis via electrodialysis.
[0053] 3. Accelerated aging cycle test: 50mA / cm 2 The system was run continuously for 100 hours, and the concentration of iron ions dissolved and the changes in transmembrane voltage were recorded.
[0054] Cathode and anode chambers: 0.5 mol / L Na₂SO₄ solution; acid and alkali chambers: initially 0.5 mol / L NaCl solution; circulating peristaltic pump speed: 60 rpm; room temperature: 25℃. Test items: ① Transmembrane voltage at the beginning and end of 100h; ② Iron ion dissolution concentration in the alkali chamber after 100h of operation (ICP-MS detection). Sample Description: Comparative example: Crosslinking by immersion in ordinary ferric chloride, without tannins, and chelated anchoring with amino-modified graphene oxide. Example 1: The bipolar membrane of the present invention (amino-functionalized graphene oxide and tannic acid dual chelate anchoring Fe) 3+ (Basic ratio) Example 2: The bipolar membrane of the present invention (optimized tannic acid addition amount, optimized anchoring system ratio) Table 3 Comparative Example 1.74 2.68 0.94 12.76 In the later stages of operation, the transmembrane voltage continued to rise, the catalytic activity declined significantly, and the alkali production rate decreased markedly. Example 1 (Basic Formulation of the Invention) 1.72 1.95 0.23 2.14 The transmembrane voltage increased slightly, iron ion dissolution was significantly suppressed, and the alkali production rate remained stable. Example 2 (Optimized formulation of the present invention) 1.71 1.86 0.15 1.23 The transmembrane voltage changes very little, the amount of iron ion dissolved is extremely low, and the water dissociation performance is stable throughout the entire process. A four-compartment electrodialysis testing apparatus was used. The cathode and anode chambers were filled with 0.5 mol / L sodium sulfate solution, while the acid and alkali chambers were filled with sodium chloride solution with an initial concentration of 0.5 mol / L. A peristaltic pump controlled the circulation flow rate in each chamber, and the current density was set to be constant at 50 mA / cm². 2 The sample was continuously subjected to constant current for 100 hours at room temperature. The initial state of the sample and the 50 mA / cm² value at the end of the 100-hour aging process were recorded. 2 The transmembrane voltage was measured. After the aging test, the alkaline chamber solution was collected, and the concentration of iron ions dissolved in the alkaline liquid phase was determined by ICP-MS inductively coupled plasma mass spectrometry.
[0055] The test results are shown in Table 3 above. The comparative example is a cross-linked bipolar membrane immersed in ordinary ferric chloride, and its Fe... 3+ The catalyst was fixed solely by the weak coordination of the carboxyl groups of polyacrylamide. After 100 hours of constant current accelerated aging, a large amount of iron ions dissolved into the alkali chamber, with an iron ion concentration of 12.76 mg / L. The transmembrane voltage increased by 0.94 V, the water dissociation catalytic activity significantly decreased, and the alkali production capacity declined.
[0056] In this invention, amino-functionalized graphene oxide is combined with tannic acid to form multiple chelating coordination sites for Fe. 3+ The water dissociation catalyst is anchored and bound. In Example 1, after 100 hours of accelerated aging, the iron ion dissolution concentration decreased to 2.14 mg / L, and the transmembrane voltage increase was only 0.23 V. In Example 2, after optimizing the chelation composition ratio, the iron ion dissolution was further reduced to 1.23 mg / L, and the transmembrane voltage increase was only 0.15 V. The water dissociation catalytic activity of the membrane can be effectively maintained under long-term electrodialysis operation conditions, significantly improving the long-term service stability of the bipolar membrane.
[0057] 4. Alkali resistance stability test: Immerse in 8 mol / L NaOH solution for 72 h and test the membrane mechanical retention rate.
[0058] Test conditions: The sample was immersed in an 8 mol / L NaOH strong alkaline solution at a constant temperature of 25℃ for 72 hours; the dry tensile strength of the membrane was tested, and the mechanical retention rate was calculated.
[0059] Sample Description: Comparative example: ordinary chitosan-PVA anionic layer; Example 1: Quaternized modified chitosan-PVA anionic layer; Example 2: Quaternization-modified chitosan-PVA membrane with optimized formulation; Testing instrument: Universal electronic tensile testing machine; Specimen specifications: width 10mm, gauge length 20mm; arithmetic mean of 5 parallel samples for each specimen.
[0060] Table 4 Comparative example (ordinary chitosan-PVA membrane) 2.12 0.41 19.3 The membrane visibly swelled and softened, with localized cracks and edge damage. Its toughness decreased significantly, and it could be easily broken with a light touch of a finger. Example 1 (Quaternized Chitosan-PVA Membrane) 2.15 1.68 78.1 The membrane swells moderately, without cracks or damage, maintains good flexibility, and exhibits no shedding or disintegration. Example 2 (Quercedamated modified chitosan-PVA membrane, optimized formulation) 2.21 1.77 80.1 The membrane is moderately swollen, with an intact surface, good flexibility, and no cracks or damage. Alkali resistance stability test: The membrane samples were cut into strips 10 mm wide and 20 mm gauge length, and divided into experimental and control groups. The samples were completely immersed in an 8 mol / L sodium hydroxide aqueous solution and soaked at a constant temperature of 25℃ for 72 h. After soaking, the samples were removed and rinsed thoroughly with deionized water until the rinse water was neutral. The surface moisture was gently absorbed with filter paper, and the dry tensile strength of the samples was tested using a universal electronic tensile testing machine. The mechanical retention rate was calculated, and the macroscopic morphology of the membrane was observed at the same time.
[0061] The test results are shown in Table 4 above. The bipolar membrane, which is the comparative example of ordinary chitosan-PVA membrane, uses an unmodified chitosan-polyvinyl alcohol system for its anion layer. After being soaked in 8 mol / L high-concentration NaOH strong alkali for 72 h, the chitosan molecular chains degraded in the strong alkaline environment, the tensile strength dropped sharply, the mechanical retention rate was only 19.3%, and the sample showed cracks and edge damage, which could no longer meet the requirements for use in electrodialysis.
[0062] The embodiments of this invention use quaternized modified chitosan, which introduces quaternary ammonium cationic groups into the chitosan molecules, significantly improving the polymer chain's resistance to strong alkali degradation; the mechanical retention rate after soaking can reach more than 78%, the membrane remains macroscopically intact without cracks or damage, and it is suitable for electrodialysis conditions with high concentrations of alkali.
[0063] 5. Interlayer peel strength test to evaluate anti-delamination performance.
[0064] Test conditions: A universal electronic tensile testing machine was used for T-peel test (180° peel); the sample width was 15 mm and the peel rate was 50 mm / min; the samples were fully soaked in 2 mol / L NaCl solution for 24 h before the test to simulate the electrolyte swelling condition; the average value of 5 parallel samples in each group was taken, and the unit was N / m.
[0065] Sample Description: Comparative example: Ordinary chitosan-PVA bipolar membrane; three layers of nanofibers were electrospun and stacked sequentially, crosslinked by glutaraldehyde vapor, with only physical stacking between layers and no interlayer covalent chemical bonding.
[0066] Example 1: The basic formulation membrane of this invention; liquid-phase crosslinking of glutaraldehyde to achieve covalent bonding between the three layers; amino-modified graphene oxide and tannic acid chelate anchoring Fe. 3+ Quaternized chitosan, glycerol-low temperature hot pressing densification complete process.
[0067] Example 2: The present invention optimizes the membrane ratio; optimizes the liquid-phase crosslinking time and concentration of glutaraldehyde to further enhance the interlayer covalent bonding.
[0068] Table 5 Comparative Example 28.6 The exfoliation interface occurs between the layers, with the interface completely separating, which is a typical example of interlayer exfoliation failure, indicating complete separation of the two nanofiber layers. Example 1 (Basic Formulation of the Invention) 87.3 The peeling process rarely occurs at the interlayer interface; it mostly occurs during fiber matrix fracture, primarily due to cohesive damage within the membrane fibers, with only localized, minute areas experiencing interfacial debonding. Example 2 (Optimized formulation of the present invention) 96.5 Almost all fractures occurred within the membrane matrix fibers, with virtually no interlayer delamination, indicating strong interlayer bonding. A universal electronic tensile testing machine was used to conduct 180°-T peel tests to evaluate the interfacial bonding performance between the intermediate nanofiber layer, cationic nanofiber layer, and anionic nanofiber layer of the bipolar membrane. The membrane was cut into 15 mm wide strips and pretreated by immersing them in a 2 mol / L sodium chloride aqueous solution for 24 h to simulate the service environment of the electrodialysis electrolyte. The peel test rate was set to 50 mm / min, with five parallel samples tested per group, and the arithmetic mean was taken as the interlayer peel strength. The peel failure morphology was observed and recorded to determine whether the failure mode was interlayer debonding or cohesive fracture of the membrane matrix itself.
[0069] The test results are shown in Table 5 above. The comparative example is a common chitosan-PVA bipolar membrane, in which three layers of nanofibers are physically stacked by electrospinning. The glutaraldehyde vapor crosslinking only acts on the interior of the anion layer, and there is a lack of covalent chemical bonding between the layers. After electrolyte swelling pretreatment, the interlayer peel strength is only 28.6 N / m, and the failure mode is complete peeling of the interlayer interface. Under repeated swelling-shrinkage cycles in the electrolyte, delamination failure is very likely to occur.
[0070] This invention employs a glutaraldehyde liquid-phase immersion crosslinking process, allowing glutaraldehyde molecules to penetrate into the interfacial region of the three-layer nanofibers. Simultaneously, they chemically react with the polymer chains of the intermediate, cationic, and anionic layers, forming covalent chemical bonds between the layers. In Example 1, the interlayer peel strength was increased to 87.3 N / m, and the failure mode shifted to cohesive fracture of most of the fiber matrix, with only localized, minor interfacial debonding. In Example 2, the crosslinking process conditions were further optimized, achieving an interlayer peel strength of 96.5 N / m, with almost no interfacial debonding. This demonstrates that the present invention significantly strengthens the interfacial bonding between the three-layer nanofibers, resisting repeated swelling-shrinkage cycles in the electrolyte and effectively suppressing interfacial delamination defects during the use of bipolar membranes.
[0071] Amino-functionalized graphene oxide chelates and coordinates with tannic acid to dual anchor Fe 3+ Catalysts address the issue of long-term iron ion leakage during current flow. Quaternization modification of chitosan enhances the anion layer's resistance to strong alkali degradation, expanding its application in high-alkali conditions. Liquid-phase glutaraldehyde immersion crosslinking replaces the glutaraldehyde vapor process, simultaneously achieving interlayer covalent bonding and resolving the swelling and delamination defects of three-layer nanofibers. Aluminum foil serves as the electrospinning receiving substrate, solving the problems of difficult peeling and tearing of nickel mesh substrates. Glycerin immersion and low-temperature, low-pressure hot pressing controllably densify the pores of nanofibers, reducing counterion leakage and improving the purity of acid and alkali production.
Claims
1. A method for preparing a highly alkali-resistant nanofiber bipolar membrane, characterized in that, Includes the following steps: S0, Raw material pre-preparation: I. Preparation of branched anionic polyacrylamide; II. Preparation of amino-functionalized modified graphene oxide; III. Preparation of quaternized modified chitosan; S1. Preparation of intermediate layer spinning solution: by mass, 1-3 parts of branched anionic polyacrylamide, 3-5 parts of linear anionic polyacrylamide, 0.3-0.5 parts of amino-functionalized modified graphene oxide, and the remainder is 50-60 wt% acetic acid aqueous solution. Electrospinning is used to spin an intermediate nanofiber substrate film on the surface of the aluminum foil receiving substrate. S2. Preparation of cationic layer spinning solution: 2-4 parts of linear anionic polyacrylamide, the remainder being 50-60 wt% aqueous acetic acid solution; electrospinning to deposit a cationic precursor nanofiber layer on the first side of the intermediate nanofiber substrate membrane; then immersing in a ferric chloride ethanol solution containing a chelating agent, tannic acid, for crosslinking; washing and drying to obtain the cationic nanofiber layer. S3. Prepare anionic layer spinning solution: 7-8 parts polyvinyl alcohol, 1-1.5 parts quaternized modified chitosan, and the remainder is 50-60 wt% aqueous acetic acid solution; electrospin to deposit anionic precursor nanofiber layer on the second side of the intermediate nanofiber substrate membrane; crosslink by liquid-phase glutaraldehyde immersion, washing and drying to obtain anionic nanofiber layer. S4. Post-treatment for controllable densification of pores: The three-layer composite nanofiber membrane is obtained and treated by soaking in glycerol-water solution, followed by low-temperature hot pressing at a temperature of 45-60℃ and a pressure of 0.2-0.5MPa. S5. Peeling: Completely peel the composite film from the aluminum foil receiving substrate; soak and activate to obtain a highly alkali-resistant nanofiber bipolar film.
2. The method for preparing a high alkali-resistant nanofiber bipolar membrane according to claim 1, characterized in that, In step S1, during the electrospinning process, the voltage is 20-25kV, the flow rate is 0.3-0.5mL / h, the receiving distance is 15-20mm, and the humidity is 50-60%.
3. The method for preparing a high alkali-resistant nanofiber bipolar membrane according to claim 1, characterized in that, In steps S2 and S3, during the electrospinning process, the voltage is 15-20kV, the flow rate is 0.5-1mL / h, the receiving distance is 10-15mm, and the humidity is 50-60%.
4. The method for preparing a high alkali-resistant nanofiber bipolar membrane according to claim 1, characterized in that, In step S0, the branched anionic polyacrylamide raw material ratio is: anionic monomers in a mass ratio of 8:2-3 acrylic acid and allyl malonic acid.
5. The method for preparing a high alkali-resistant nanofiber bipolar membrane according to claim 1, characterized in that, In step S0, during the preparation of the amino-functionalized modified graphene oxide, the graphene oxide is first alkenylated, then grafted with amino-containing monomers, resulting in a surface rich in amino chelation sites and multiple chelation fixation of Fe. 3+ .
6. The method for preparing a high alkali-resistant nanofiber bipolar membrane according to claim 1, characterized in that, In step S0, the quaternized chitosan is modified with 2,3-epoxypropyltrimethylammonium chloride grafted onto chitosan to improve its alkali resistance and anion exchange sites.
7. The method for preparing a high alkali-resistant nanofiber bipolar membrane according to claim 1, characterized in that, In step S2, the FeCl3 mass fraction in the ferric chloride ethanol solution is 8-10 wt%, and the amount of tannic acid added is 15-25 wt% of the FeCl3 mass; the crosslinking time is 10-12 min.
8. The method for preparing a high alkali-resistant nanofiber bipolar membrane according to claim 1, characterized in that, In step S3, during the glutaraldehyde liquid phase immersion crosslinking process, 45-50 wt% glutaraldehyde aqueous solution is used for immersion for 8-10 min.
9. A highly alkali-resistant nanofiber bipolar membrane, prepared according to any one of claims 1 to 8, characterized in that, Membranes include: The three layers consist of a middle nanofiber layer, a cationic nanofiber layer, and an anionic nanofiber layer, with covalently bonded interfaces between them. Amino-functionalized modified graphene oxide is dispersed within the middle layer. Fe... 3+ Anchored on modified graphene oxide through multiple chelation sites, the anionic layer is a quaternized modified chitosan-polyvinyl alcohol crosslinked network; The membrane undergoes low-temperature hot-pressing densification treatment; the membrane porosity is 35-50%.
Citation Information
Patent Citations
A nanofiber-reinforced bipolar membrane and its preparation method
CN121422740B